ANALISIS FRAMING PEMBERITAAN POLITIK DINASTI JOKOWI PADA PEMILIHAN KEPALA DAERAH SERENTAK TAHUN 2020 DI MEDIA ONLINE - Abdul Aziz; Umaimah Wahid (Metacommunication: Journal of Communication Studies, 2021)
Dynastic politics has always been an issue that has attracted public attention to be discussed during the Regional Head Election (Pilkada) process. This is because in reality there is a tendency in many regional heads to try to build dynastic politics. The simultaneous Regional Head Election (Pilkada) in 2020 is quite interesting with several candidates emerging from the family of President Jokowi. This study aims to determine how online media of kompas.com and okezone.com in framing news about dynastic politics in the 2020 Pilkada. To achieve this goal, this study uses a qualitative research method, where the author uses the framing analysis model of Robert N. Entmant. The object of this research is news regarding the politics of President Jokowi's dynasty, in online media kompas.com and okezone.com. The data collection technique used literature study. The results of the analysis of this study present news about dynastic politics in the 2020 Pilkada. In the results of the news framing analysis using the Robert N. Entman model, there are several stages such as problem definition, problem estimation from problem sources, moral decision making, and problem solving. The news on kompas.com clearly highlighted news that was contra or disagreeable with the existence of dynastic politics in Indonesia, especially in the 2020 Pilkada, while the news on okezone.com clearly did not question the existence of dynastic politics in the 2020 Pilkada. The victory of the two PDI-Perjuangan candidates is part of the General Chair's commitment to ensure that his party leads to produce quality young leadership. Of course, the imbalance in the selection of sources in the news is very important so that people who see it can provide a more objective opinion of the news.